Epidemiology of leukemia and lymphoma : report of the Leukemia Research Fund International Workshop, Oxford, UK, September 1984 - Greaves, M. F. (Melvyn F.), 1941-; Chan, L. C. (Pergamon Press, 1985)
Epidemiology of Leukaemia and Lymphoma contains the proceedings of the Leukaemia Research Fund International Workshop held in Oxford, UK, on September 25-27, 1984. Contributors explore the epidemiology of leukemia and lymphoma based on the results of a pilot study that investigated whether careful subdivision of acute lymphoblastic leukemia (ALL) using a standardized panel of monoclonal antibodies would reveal interesting associations between subtypes and particular geographic regions or ethnic groups within regions. This book is comprised of 31 chapters divided into four sections and begins w.